Hubungan Kebiasaan Merokok Dengan Kejadian Tuberculosis Paru Pada Pasien Dewasa Di Wilayah Kerja Puskesmas Telaga Dewa Dan Puskesmas Sawah Lebar Kota Bengkulu Tahun 2024 - Fernandes, Brilian; Handayani , Tita Septi; Aprianti, Delta (CV. Utami, 2025)
Pulmonary tuberculosis remains a major health issue worldwide, with an increase every year. Tuberculosis is an infectious disease caused by the Mycobacterium Tuberculosis (MTB) bacteria, which can spread through the air from one person to another. This study aims to determine the relationship between smoking habits and lung tuberculosis incidence in adult patients in the Working Area of Telaga Dewa and Sawah Lebar Public Health Centers, Bengkulu City. The method used is an analytical observational research design with a case-control approach. Data were collected by distributing questionnaires to 54 respondents with lung tuberculosis and 54 individuals who do not have lung tuberculosis at Telaga Dewa and Sawah Lebar Health Centers using total sampling technique. The results showed that from 54 respondents in the case group with light smoking habits, there were 14 (25.9%) respondents who experienced lung tuberculosis. From 54 respondents in the control group with light smoking habits, 28 (51.9%) respondents did not experience lung tuberculosis. There is a significant relationship between smoking habits and the incidence of lung tuberculosis (p-value < 0.022). It is recommended that the results of this study be used as information and consideration in addressing issues within health programs related to lung tuberculosis in the Working Area of Telaga Dewa and Sawah Lebar Health Centers, Bengkulu City.